2022
DOI: 10.1096/fasebj.2022.36.s1.r2759
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Gut Microbiome Composition with Healthy Aging in Humans: Links to Vascular Endothelial Function

Abstract: Aging is the primary risk factor for cardiovascular diseases, primarily due to development of vascular endothelial dysfunction. The gut microbiome is a strong influencer of host physiology, but few studies have investigated how gut microbiome composition changes with primary (healthy) aging in humans, or how such changes may influence endothelial function. PURPOSE To: 1) determine changes in gut microbiome composition and their relation to endothelial function in healthy late middle‐aged to older (MA/O) vs. yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…243 Further, a small but growing body of translational evidence has indicated that gut microbial diversity and intestinal permeability contribute to age-related vascular dysfunction in people without HIV. [244][245][246][247] For example, both α-and β-diversity have been reported to be inversely related to FMD in adults. 245 In support of these findings, Menni et al 246 reported a significant, independent, inverse relation between α-diversity and cfPWV in women from the Twin-sUK cohort study.…”
Section: Hiv Gut Dysbiosis and Host Immune Cell Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…243 Further, a small but growing body of translational evidence has indicated that gut microbial diversity and intestinal permeability contribute to age-related vascular dysfunction in people without HIV. [244][245][246][247] For example, both α-and β-diversity have been reported to be inversely related to FMD in adults. 245 In support of these findings, Menni et al 246 reported a significant, independent, inverse relation between α-diversity and cfPWV in women from the Twin-sUK cohort study.…”
Section: Hiv Gut Dysbiosis and Host Immune Cell Interactionsmentioning
confidence: 99%
“…[244][245][246][247] For example, both α-and β-diversity have been reported to be inversely related to FMD in adults. 245 In support of these findings, Menni et al 246 reported a significant, independent, inverse relation between α-diversity and cfPWV in women from the Twin-sUK cohort study. Therefore, this emerging body of evidence describes an important gut-immune-vascular axis and implicates adverse changes in gut microbiome composition and intestinal permeability as potential contributors to age-related vascular dysfunction in PLWH.…”
Section: Hiv Gut Dysbiosis and Host Immune Cell Interactionsmentioning
confidence: 99%